The contribution of σ70 and σN factors to expression of class II pilE in Neisseria meningitidis - Lobanovska, M; Tang, CM; Exley, RM (American Society for Microbiology, 2019)
Neisseria meningitidis expresses multi-component organelles called Type four pili (Tfp), which are key virulence factors required for attachment to human cells during carriage and disease. Pilin (PilE) is the main component of Tfp and N. meningitidis isolates have either a class I pilE locus and express pilins that undergo antigenic variation, or a class II pilE locus and express invariant pilins. The transcriptional regulation of class I pilE has been studied in both N. meningitidis and Neisseria gonorrhoeae, while the control of expression of class II pilE has been elucidated in the non-pathogenic Neisseria elongata. However, the factors that govern the regulation of the class II pilE gene in N. meningitidis are not known. In this work, we have bioinformatically and experimentally identified the class II pilE promoter. We confirmed the presence of conserved σ70 and σN-dependent promoters upstream of pilE in a collection of meningococcal genomes and demonstrate that class II pilE expression initiates from the σ70 family-dependent promoter. By deletion or overexpression of sigma factors, we show that σN, σH and σE do not affect class II pilin expression. These findings are consistent with a role of the housekeeping σD in expression of this important component of Tfp. Taken together our data indicate that the σ-dependent network responsible for the expression of class II pilE has been selected to maintain pilE expression, consistent with the essential roles of Tfp in colonisation and pathogenesis.